2008
DOI: 10.1364/ol.33.000518
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot extreme ultraviolet laser imaging of nanostructures with wavelength resolution

Abstract: We have demonstrated near-wavelength resolution microscopy in the extreme ultraviolet.Images of 50 nm diameter nanotubes were obtained with a single ~1 ns duration pulse from a desk-top size 46.9 nm laser. We measured the modulation transfer function of the microscope for three different numerical aperture zone plate objectives, demonstrating that 54 nm half-period structures can be resolved. The combination of near-wavelength spatial resolution and high temporal resolution opens myriad opportunities in imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…In the compact EUV microscope utilizing a Fresnel optic, described in Section 5, the coherence of the source can be problematic due to coherence effects present in the microscope image, related to the properties of the laser beams [41]. Thus, for EUV imaging using the zone−plates, a compact laser plasma EUV source based on a double stream gas−puff target, presented in Fig.…”
Section: Euv Sourcesmentioning
confidence: 99%
“…In the compact EUV microscope utilizing a Fresnel optic, described in Section 5, the coherence of the source can be problematic due to coherence effects present in the microscope image, related to the properties of the laser beams [41]. Thus, for EUV imaging using the zone−plates, a compact laser plasma EUV source based on a double stream gas−puff target, presented in Fig.…”
Section: Euv Sourcesmentioning
confidence: 99%
“…The diffraction limit of UV lights itself is down to 100 nm without a near-field probe. It has been reported that a compact capillary discharge UV laser can realize an imaging with a spatial resolution of 120-150 nm [86,87].…”
Section: Near-field Experiments In Thz Regionmentioning
confidence: 99%
“…Employing such radiation allows to visualize in a direct way through absorption contrast mechanism the flow of the gas, usually investigated with other techniques, such as the interferometry [10]. It was demonstrated that the radiation from a capillary discharge laser operating at a wavelength of = 46.9 nm EUV images permits to obtain a spatial resolution better than 55 nm [11,12], and that the spatial resolution of holographic images [13], employing the same EPJ Web of Conferences 167, 03001 (2018) https://doi.org/10.1051/epjconf/201816703001 PPLA 2017 wavelength, can be improved up to sub-50 nm [14]. A table top EUV laser emitting 13.2 nm wavelength radiation from Ni-like Cd ions was employed for imaging of with a sub-38 nm spatial resolution and a picosecond time resolution [15].…”
Section: Introductionmentioning
confidence: 99%